Karakteristik Oseanografi Fisika Pantai Pandan Tapanuli Tengah Sumatera Utara - Sakkeus Harahap; Mubarak '; Musrifin Galib (Universitas Riau, 2009)
This research was conducted from 14 – 28, May 2009 at Kelurahan Pandan Central Tapanuli of North Sumatra Province. The method used in this research is surveymethod. research results indicate that the characteristics of waves in coastal watersthere is Pandan wave breaking before reaching the coastline and affected by theshallow depth and tide, the flow velocity at the time of pairs ranged from 0,04 to0,23 m / s and at low tide ranged from 0,11 – 0,48 m / s. Type of tide in coastalwaters is a type of mixed biased doubles daily. In a day happens twice for both tideand ebb with the different of time and height. Pandan beach slope is gently slopingbeach that ranges from 0.9 - 1.9%.Keywords : Characteristic, wave, current and tide